دراسة بعض العوامل المؤثرة على إنتشار اليرقان بين حديثي الولادة: دراسة ميدانية داخل قسم حديثي الولادة مستشفى صبراتة التعليمي - سهام رمضان الزهاني; نجلاء مصطفى السائح (Surman Journal of Science and Technology, 2024)
This study aims to identify the prevalence of jaundice among newborns at Sabratha Teaching Hospital, to identify maternal demographic and biological factors that may contribute to an increased likelihood of jaundice in newborns, to determine newborn-related factors such as gestational age, birth weight, and sex, and their impact on the occurrence of jaundice, and to analyze the role of medical and clinical factors, including type of delivery, blood type incompatibility (ABO and Rh), and co-morbidities, in the prevalence of jaundice. This study collected data from 30 newborns in the neonatal unit of Sabratha Teaching Hospital, from 9-12-2023, who were diagnosed with neonatal jaundice and registered in the unit’s records during the study period. The study employed a descriptive-analytical approach, reviewing the statistical records of newborns in the neonatal unit. Researchers identified the data they wished to collect to achieve the study’s objectives, and these variables included: infant sex, infant age in hours (48-72 hours), infant weight at birth, serum bilirubin level, gestational age (full term/premature), time of initiation of breastfeeding, infant blood type, maternal blood type, and severity of jaundice. The study concluded that neonatal jaundice was more common in males than females. The highest percentage of jaundice cases was recorded within the first 72 hours after birth. The results also showed that most affected infants were of normal weight and full term. Furthermore, bilirubin levels were within the moderate range for the majority of cases, indicating physiological jaundice in the sample. The results showed that blood type A+ was the most common among both infants and mothers. However, no statistically significant relationship was found between blood type (of the infant or mother) and the severity of the condition. The t-test results did not show statistically significant differences between males and females in bilirubin levels, weight, or gestational age.